Crystal Structure, Sensitiveness and Theoretical Explosive Performance of Xylitol Pentanitrate (XPN). Issue 5 (22nd March 2019) - Stark, Kelly‐Anne S.; Alvino, Jason F.; Kirkbride, K. Paul; Sumby, Christopher J.; Metha, Gregory F.; Lenehan, Claire E.; Fitzgerald, Mark; Wall, Craig; Mitchell, Mark; Prior, Chad
Abstract: Xylitol pentanitrate (XPN) is a little‐studied nitrate ester of similar molecular structure to the military energetic materials pentaerythritol tetranitrate (PETN) and nitroglycerin (NG). XPN was crystallised from a mixture of ethanol and water by slow evaporation and studied by single crystal X‐ray diffraction. XPN crystallises in the centrosymmetric monoclinic space group P21 /n, with a calculated density of 1.852 g cm −3 . Sensitiveness analysis of the energetic material revealed it to be a primary explosive, significantly more sensitive than PETN to friction and impact. The calculated heat of formation of XPN, −500.48 kJ mol −1, and the density were exploited utilising the Cheetah 7.0 suite of programs to predict explosive performance parameters. The theoretical explosive performance of XPN was comparable to the calculated explosive parameters of erythritol tetranitrate (ETN), PETN and cyclotrimethylene trinitramine (RDX). Abstract :